The influence of trust, convenience, and quality information on purchase decisions at marketplace shopee in Sukabumi - Pipit Eriyanti; Andri Ardhiyansyah (Forum Kerjasama Pendidikan Tinggi, 2023)
This study aims to determine the effect of trust, convenience, quality of information on purchase decisions at the shopee marketplace (a case study of the Sukabumi community). The research population is consumers who have made purchases online at the shopee site. The sample is 55 people using purposive sampling method. Data collection is carried out using a questionnaire. Data were analyzed using multiple linear regression analysis using the SPSS program. The results of the research show that Trust has a positive and significant effect on purchase decision, convenience has a positive and significant effect on purchase decision, information quality has a positive and significant effect on purchase decision